Cemitério municipal de Cruz Alta: memória e patrimônio atrás da murada de pedras. a preservação do espaço cemiterial - Pereira, Juliana de Fátima Abreu de Oliveira (2022)
The present research has as object of study the Municipal Cemetery of Cruz Alta, and the empirical intention of the study is to encourage the population of the city of Cruz Alta to value their funerary heritage, through heritage education and cemetery tourism. The intention is to show the cemetery space as a possibility of tourist attraction, highlighting the collective memory and its relationship with the local and national social and historiographic construction. For this, the aspects of the constitution of the municipality, the relationship of the construction of the secularized cemetery, its relationship with the citizens, and their interaction with the cemetery space are analyzed. It is considered that it has ample potential for the development of cemetery tourism, taking into account the weave between life and death present therein. Thus, it is extremely feasible that the space becomes a tourism option, promoted through heritage education and visitation circuits to the cemetery with a Visitor's Guide to the space.